2005
DOI: 10.1515/sug-2005-0103
|View full text |Cite
|
Sign up to set email alerts
|

Die Welt der Ultras. Eine neue Generation von Fußballfans / The World of the Ultras. A New Generation of Football Fans

Abstract: ZusammenfassungMit der Ultra-Bewegung hat sich in den letzten Jahren eine neue Generation von Fußballfans in den Stadien zu Wort gemeldet, deren erlebnisorientierte und widerspenstige Inszenierungen zugleich als Medium und als Motor von Wandlungstendenzen der Fankultur interpretiert werden können. Die Ultras weisen dabei eine ausgeprägte Tendenz zur Selbstdarstellung und Selbstmediatisierung auf. Sie sind eine ausgeprägt öffentlichkeitsorientierte Subkultur, die nicht nur in der Fankurve des Stadions den Ton a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Secondly, research into the most recent developments in soccer fan scenes have shown that the "Ultras" (the fan groups that consider themselves the truest, most sincere, and most devoted) maintain a certain implicit political agenda, which is, nowadays, often rather left-leaning, sometimes even radical left (Langer, 2010;Schwier, 2005). Also, "traditional" hooliganism and right-wing fan sub-cultures with nationalist and/or racist undertones continue to exist in Germany, though they have considerably lost ground since their heydays in the 1980s and 1990s.…”
Section: "Like Windup Dolls": German Media Coverage Of Religious Athlmentioning
confidence: 99%
“…Secondly, research into the most recent developments in soccer fan scenes have shown that the "Ultras" (the fan groups that consider themselves the truest, most sincere, and most devoted) maintain a certain implicit political agenda, which is, nowadays, often rather left-leaning, sometimes even radical left (Langer, 2010;Schwier, 2005). Also, "traditional" hooliganism and right-wing fan sub-cultures with nationalist and/or racist undertones continue to exist in Germany, though they have considerably lost ground since their heydays in the 1980s and 1990s.…”
Section: "Like Windup Dolls": German Media Coverage Of Religious Athlmentioning
confidence: 99%